Influence of titanium dioxide nanoparticles on 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin bioconcentration and toxicity in the marine fish European sea bass (Dicentrarchus labrax). (January 2015) - Della Torre, Camilla; Buonocore, Francesco; Frenzilli, Giada; Corsolini, Simonetta; Brunelli, Andrea; Guidi, Patrizia; Kocan, Anton; Mariottini, Michela; Mottola, Filomena; Nigro, Marco; Pozo, Karla; Randelli, Elisa; et al.
Abstract: The present study investigated the influence of nano-TiO2 (1 mg L −1 ) on 2, 3, 7, 8-tetrachlorodibenzo- p -dioxin (2, 3, 7, 8-TCDD) (46 pg L −1 ) bioconcentration and toxicity in the European sea bass ( Dicentrarchus labrax ) during 7 days in vivo exposure. A multimarkers approach was applied in different organs: detoxification in liver; innate immunity and pro-inflammatory response and adaptive immunity in gills and spleen; genotoxicity in peripheral erythrocytes and muscle. Bioconcentration of 2, 3, 7, 8-TCDD in presence of nano-TiO2 was investigated in liver, skin and muscle as well as interaction between nano-TiO2 and organic pollutants in artificial sea water (ASW). Nano-TiO2 negatively influenced immune response induced by 2, 3, 7, 8-TCDD in spleen but not in gills and reduced the DNA damage induced by 2, 3, 7, 8-TCDD in erythrocytes. nano-TiO2 did not interfere with 2, 3, 7, 8-TCDD detoxification and bioconcentration according to the observed no interaction of the nano-TiO2 with organic pollutants in ASW. Graphical abstract: Highlights: Nano-TiO2 did not interfere with 2, 3, 7, 8-TCDD detoxification and bioconcentration in liver. Nano-TiO2 affected immune response towards 2, 3, 7, 8-TCDD exposure in spleen. Co-exposure caused a reduction of DNA strand breaks respect to single chemicals exposure. Nano-TiO2 alone and combined with 2, 3, 7, 8-TCDD increased MN frequencies in erythrocytes. Abstract : The present study provides first evidence on the toxic effects of nano-TiO2 in the marine fish Dicentrarchus labrax highlighting nano-TiO2 influence on 2, 3, 7, 8-TCDD bioconcentration and toxicity.